Variação das vogais médias pretônicas em textos antigos: contribuições da teoria neogramática e da difusão lexical - Ribeiro, Tatiana Jimenes Silveira (2018)
With regards to the vowel system, this research seeks to understand the vowel variations of Portuguese through the incidence of phonological processes of vocal harmony, raising without apparent motivation and lowering vowel frequent in ancient texts written in Rio Grande do Sul. The study is focused on the variations of the pretonic mid-vowels that can be explained according to two distincts theories of linguistic change, as in the scope of the neogrammatical rule or as a diffusionist phenomenom. The aim of this study is to analyze the occurrences of replacements in pretonic vowels and discuss whether they can be explained like a phenomenom of articulatory origin, explainable and/or as a change of lexical imprint. It is well known that the imbalance of the pretonic mid-vowels is common in the language since the archaic Portuguese. Therefore, it was found in the old manuscripts, the variation of the pretonic mid-vowels, as recorded in the words fiminino (VH), mutivo (VH), descuberta (RA), destrito (LO). The research of the corpus comprises 19 facsimile and/or diplomatic editions of documents from XIX and early XX century, which belong to Arquivo Histórico Municipal de Santa Maria, Casa de Memória Edmundo Cardoso, Arquivo Histórico de Cachoeira do Sul, Arquivo Histórico do Rio Grande do Sul and Projeto Português Histórico do Rio Grande do Sul, coordinated by Dra. Evellyne Costa (UFSM). We considered whether it is possible to analyze the variation of the pretonic vowels as a neogrammatical rule and as a lexical diffusion, since the data present that there are signs for the rule of vocal harmony, as the presence of the high vowel in the following syllable, of the lowering vowel and raising of the pretonics without the presence of the high vowel in the adjacent syllable, the main trigger of the raising. As a proposal, it has been suggested a combined analysis of the theories in order to better understand the phenomena studied.